Attitudes and Commitment Toward Precautionary Measures Against COVID-19 Amongst the Jordanian Population: A Large-Scale Cross-Sectional Survey - Moawiah Khatatbeh (Frontiers Media S.A., 2021)
Aims: This study aimed to (1) assess the non-pharmaceutical intervention (NPI) measures that were used by the Jordanian population against COVID-19, and (2) determine the sociodemographic and behavioral predictors of contracting COVID-19 with a focus on the utilization of personal precautionary measures.Methods: A descriptive questionnaire-based cross-sectional survey was used in this study. A structured web-based questionnaire was disseminated to the Jordanian community through social media platforms. Participants were asked a series of questions about socio-demographic characteristics, in addition to the knowledge, attitudes, and commitment toward using various personal precautionary measures (e.g., face mask, hand washing, social distancing) against the COVID-19. Data were analyzed using descriptive statistics, cross-tabulation, and binary logistic regression through SPSS®.Results: Responses from 7,746 participants were included in our final analyses. Descriptive statistics showed that most participants (82.6%) believed that face mask protects against COVID-19. Around 69.5% of the participants were completely committed to wearing a face mask, while 65% of the participants were completely committed to hand washing. The results of the regression analysis revealed that female gender (AOR = 1.2; 95% CI: 1.07–1.35; p = 0.002), having a family member infected with COVID-19 (AOR = 8.5; 95% Cl: 7.51–9.70; p = 0.001), having a health-related work or study (AOR = 1.2; 95% Cl: 1.09–1.38; p = 0.001), believing that face masks do not protect against COVID-19 (AOR = 1.3; 95% Cl: 1.12–1.47; p = 0.001), and partial commitment to handwashing (AOR = 1.2; 95% Cl: 1.11–1.75; p = 0.006) were all associated with an increased odds of contracting COVID-19 among the participants.Conclusion: Overall, commitment to non-pharmaceutical intervention (NPI) measures, such as wearing a face mask, hand washing, and physical distancing, was not optimal among Jordanians. This might explain the dramatic increase in the infectivity rate of the COVID-19 virus in the past few months in the country. More sustainable efforts regarding health promotion and strict policies are required to prevent a third wave of hitting the country and to prevent similar infectious threats in the future.